IGFBP-4: A PROMISING BIOMARKER FOR LUNG CANCER - Savas, Irem Nur; Ozturk, Akin; Kavas, Murat; Bulut, Ismet; Alparslan, Sumeyye; Eroglu, Selma Aydogan; Baytemir, Cansel Atinkaya; Kolay, Murat; Coskun, Abdurrahman (SOC MEDICAL BIOCHEMISTS SERBIA, 2021)
Background: Insulin-like growth factor binding protein-4 (IGFBP-4), a member of the insulin-like growth factor (IGF) family, transports, and regulates the activity of IGFs. The pregnancy-associated plasma protein-A (PAPP-A) has proteolytic activity towards IGFBP-4, and both proteins have been associated with a variety of cancers, including lung cancer. Thus, we aimed to evaluate the use of IGFBP-4 and PAPP-A as potential biomarkers for lung cancer. Methods: Eighty-three volunteers, including 60 patients with lung cancer and 23 healthy individuals, were included in this study. The patients with lung cancer were selected based on their treatment status, histological subgroup, and stage of the disease. Enzyme-linked immunosorbent assays were used to assess the serum levels of IGFBP-4 and PAPPA, whereas the IGF-1 levels were measured using a chemiluminescent immunometric assay. Results: The serum IGFBP-4 levels in all patient groups, regardless of the treatment status and histological differences, were significantly higher than those in the control group (p < 0.005). However, the serum PAPP-A levels in the untreated patient group were found to be higher than those in the control group, but this difference was not statistically significant (p = 0.086). Conclusions: The serum PAPP-A and IGFBP-4 levels are elevated in lung cancer. However, IGFBP-4 may have better potential than PAPP-A as a lung cancer biomarker.
Keywords: lung cancer; biomarkers; IGFBP-4; PAPP-A; IGF-1